2016
DOI: 10.1017/ice.2016.198
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Overall and Multidrug-Resistant Organism Bioburden on Environmental Surfaces in Healthcare Facilities

Abstract: OBJECTIVE To determine the typical microbial bioburden (overall bacterial and multidrug-resistant organisms [MDROs]) on high-touch healthcare environmental surfaces after routine or terminal cleaning. DESIGN Prospective 2.5-year microbiological survey of large surface areas (>1,000 cm2). SETTING MDRO contact-precaution rooms from 9 acute-care hospitals and 2 long-term care facilities in 4 states. PARTICIPANTS Samples from 166 rooms (113 routine cleaned and 53 terminal cleaned rooms). METHODS Using a standard s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 35 publications
2
76
2
1
Order By: Relevance
“…For comparison, a 2.5-year multicenter prospective survey of high-touch surfaces in patient rooms found that~40% of the rooms examined were contaminated with MDROs, including Gram-positive and Gram-negative organisms such as vancomycin-resistant enterococci, methicillin-resistant Staphylococcus aureus, MDR K. pneumoniae, and MDR A. baumannii. We did not investigate Gram-positive organisms in this study; furthermore, WGS was not used to investigate genetic relatedness in that study, so the possible comparisons of studies are limited (56).…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, a 2.5-year multicenter prospective survey of high-touch surfaces in patient rooms found that~40% of the rooms examined were contaminated with MDROs, including Gram-positive and Gram-negative organisms such as vancomycin-resistant enterococci, methicillin-resistant Staphylococcus aureus, MDR K. pneumoniae, and MDR A. baumannii. We did not investigate Gram-positive organisms in this study; furthermore, WGS was not used to investigate genetic relatedness in that study, so the possible comparisons of studies are limited (56).…”
Section: Discussionmentioning
confidence: 99%
“…56 The viability of resistant organisms on fomites in the hospital environment is estimated from experimental studies, but is likely affected by many confounding factors (eg, organism burden and strain, temperature, moisture). Some resistant nosocomial pathogens are notoriously hardy on dry surfaces, including VRE and MRSA.…”
Section: Management Of Antibiotic-resistant Organism Colonizationmentioning
confidence: 99%
“…a composite). 4,6 Due to right hand dominance, bacteria may have been more likely to be removed from that side of the HTS during cleaning. To avoid introducing a systematic bias, alternating sides of the HTS were sampled by each method.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Identification and antimicrobial susceptibility testing of recovered organisms were performed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (Bruker Daltonics Inc.) and via the BD Phoenix™ Automated Microbiology System, respectively. 4 Enterobacteriaceae resistant to at least ertapenem were identified as CRE.…”
Section: Methodsmentioning
confidence: 99%